ZISWAF Baitulmaal Management Strategy of Modern Mosque Kurir Langit for Mosque and Ummah Empowerment - Nursyahid M., A. Muh. (International Journal of Science and Society, 2025)
This study aims to (1) Explain the mosque-based baitulmal strategy at the Kurir Langit Modern Mosque, so that it can be a reference for the development and management of other mosques; (2) Know the baitulmal strategy of the Kurir Langit Modern Mosque in empowering the mosque and empowering the ummah. This research uses the type of field research, which is research that intends to understand the phenomenon of what is experienced by the research subject. The results of this study indicate that 1) The Mosque Baitulmal strategy at the Kurir Langit Modern Mosque is implemented as a ZISWAF collection, management and distribution Lembagaon. Takmir mosque as amil zakat and nadzir waqf. So that this research finds differences in implementation with other mosques and LAZIS so that social charity programs, waqf charities, da'wah & mosque charities, business charities, and educational charities are realized. 2) The Mosque empowerment strategy of Baitulmal Masjid contributes in the form of Ubudiyah Role, Tarbiyah Role, and the Role of Ijtimaiyah.